Screening for Tuberculosis in Migrants: A Survey by the Global Tuberculosis Network - Lia D'Ambrosio; Rosella Centis; Claudia C. Dobler; Simon Tiberi; Alberto Matteelli; Justin Denholm; Dominik Zenner; Seif Al-Abri; Fatma Alyaquobi; Marcos Abdo Arbex; Evgeny Belilovskiy; François-Xavier Blanc; et al. (MDPI AG, 2021)
Tuberculosis (TB) does not respect borders, and migration confounds global TB control and elimination. Systematic screening of immigrants from TB high burden settings and-to a lesser degree TB infection (TBI)-is recommended in most countries with a low incidence of TB. The aim of the study was to evaluate the views of a diverse group of international health professionals on TB management among migrants. Participants expressed their level of agreement using a six-point Likert scale with different statements in an online survey available in English, French, Mandarin, Spanish, Portuguese and Russian. The survey consisted of eight sections, covering TB and TBI screening and treatment in migrants. A total of 1055 respondents from 80 countries and territories participated between November 2019 and April 2020. The largest professional groups were pulmonologists (16.8%), other clinicians (30.4%), and nurses (11.8%). Participants generally supported infection control and TB surveillance established practices (administrative interventions, personal protection, etc.), while they disagreed on how to diagnose and manage both TB and TBI, particularly on which TBI regimens to use and when patients should be hospitalised. The results of this first knowledge, attitude and practice study on TB screening and treatment in migrants will inform public health policy and educational resources.